The Effect of Free Shipping Promos and Customer Reviews on Purchasing Decisions of Shopee E-Commerce Users in the City of Bandung on Twin Date Events - Hariyanto, Hariyanto (Dinasti Publisher, 2023)
The competitive e-commerce market drives platforms like Shopee to understand the factors that influence users' purchasing decisions. Special events such as twin dates create their own opportunities and challenges. This study aims to analyse the impact of free shipping promos and customer reviews on the purchasing decisions of Shopee users in Bandung City during the twin dates event. Using Nonprobability Sampling technique and purposive sampling sub-technique, this study found that free shipping promos and customer reviews have a significant effect on purchasing decisions. The findings are expected to provide insights for Shopee and other e-commerce platforms in optimising their marketing strategies, increasing competitiveness, and responding more effectively to the growing demand from online consumers.